Accuracy and Automatic Computation of Seismic Refraction: a case of Forward Modeling and Inversion - Hiden, Hiden; B, Kirbani S; S, wiwit; S, Hadmoko D; Setiawan, Ari (Gravitasi, 2014)
It has been built a data processing program to perform the first arrival waktu tempuh inversion of seismic refraction profiles zero distance. Analysis of the first wave arrival time is obtained by 1) using two-way analysis of time-taking to control the accuracy of the passage and identify the mistakes geometry,, 2) parameterization slowness and intercept-time of travel-time, in which the velocity model and multi-layer thickness obtained by inversion LSQ method (unconstrained, constrained and Marquardt) on seismic refraction. For automatic calculation and accurate, we make a data processing program for the third inversion LSQ method. Analysis of the model resolution and measurement data to determine the optimal parameters of the model, the algorithm used Menke (1989). Resolution inversion results, we tested with: forward modeling, the level of misfit (error) and the convergence between the observed data and the model. Once the program is successfully tested on a number of data, then we apply to the real seismic. The results of field data inversion interpreted that the subsurface strata bedding row from the top (first layer) in the form of: soil, sand (loose), sand (saturated, loose) and sandstone, limestone. Resolution velocity and thickness in the forward modeling program: a) the error between: 10-17 - 10-5 and b) the residue of convergence is: 10-11-10-4, while the resolution of the results of the third inversion LSQ method on the field data, obtained misfit between: 10-17 - 10-4 and residual convergence between measurement data and the model are: 10-11 -10-4.Keywords —seismic refraction, forward modeling, LSQ inversion, parameter models, resolution.